A case report on the impact of a digital health intervention in the integrated care management for IBS in India - Reddy, P Rohan; Chan, N V N P Sai Sarath; Charugulla, Sujeet Narayan; Agarwal, Sony; Kotak, Bhavesh P (Indian Journal of Case Reports, 2025)
Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder characterized by abdominal discomfort and altered bowel habits. Despite its prevalence, IBS remains challenging due to its multifactorial pathophysiology. Digital health interventions offer novel solutions, integrating dietary, psychological, and wellness interventions. This case report explores the use of the DailyBloom IBS App in managing IBS in a patient with IBS diarrhea-predominant. This patient underwent a structured 14-week program that included a low-FODMAP diet, cognitive behavioral therapy, and physical wellness therapy modules through a smartphone application. The patient noted significant improvement in abdominal pain, bloating, and diarrhea frequency. Improvements were also observed in quality-of-life measures, anxiety, and stress levels, with adherence facilitated by the app’s tracking features. The patient’s symptoms improved substantially from baseline, reflecting overall symptom relief and lifestyle improvement.